2020 IEEE 28th International Requirements Engineering Conference (RE) 2020
DOI: 10.1109/re48521.2020.00018
|View full text |Cite
|
Sign up to set email alerts
|

Voice of the Users: A Demographic Study of Software Feedback Behaviour

Abstract: User feedback on mobile app stores, product forums, and on social media can contain product development insights. There has been a lot of recent research studying this feedback and developing methods to automatically extract requirement-related information. This feedback is generally considered to be the "voice of the users"; however, only a subset of software users provide online feedback. If the demographics of the online feedback givers are not representative of the user base, this introduces the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For instance, studies interviewed practitioners to understand how user feedback is captured and used by software engineers for specific tasks, such as verification and validation [46]; and they found that many practitioners still use a manual approach for collecting feedback and that the exploitation of feedback in their software development process is still not systematic [85]. Other interviews with practitioners highlight the importance that software developers give to user reviews in app stores to guide the design and evolution of their apps [13], [84].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies interviewed practitioners to understand how user feedback is captured and used by software engineers for specific tasks, such as verification and validation [46]; and they found that many practitioners still use a manual approach for collecting feedback and that the exploitation of feedback in their software development process is still not systematic [85]. Other interviews with practitioners highlight the importance that software developers give to user reviews in app stores to guide the design and evolution of their apps [13], [84].…”
Section: Introductionmentioning
confidence: 99%
“…Despite of the fact CloudComputing(CC)applicationsandservicesgohandinhand,thecloudapplicationsare notdesignedfromacustomer'sperspective.Userinvolvementinsoftwaredevelopmenthasbeen thesubjectofimportantresearchandhasbeenacknowledgedintuitivelyandaxiomaticallyto playanimportantroleinthesatisfactionofusers,contributingtosystemsuccess (Bano,2015). Thereisaseveralkindsofuser'sinvolvementamongothers,pastusers'feedback (Tizard,Rietz, &Blincoe, 2020) reviews, suggestions and comments from online sites. A multi-perspective approach to RE can potentially lead to specifications of requirements that are more likely to meettheneedsofavarietyofsystemstakeholders.VORD(Viewpoint-OrientedRequirement Definition) (Kotonya, & Sommerville, 1996) is an adaptation of the use of perspectives for REthatdoesnotsuggestanyuniqueformofpointofviewornotation.TheVORDmethodis proposedtoelicit,analyze,anddocumenttherequirementsforaService-OrientedSystem(SOS) (Sommerville,&Sawyer,1998).Theorigins of requirementsmaybefrom stakeholders,other systemsthatcommunicatewiththeproposedsystem,orfromotherorganizationsintheproposed systemsenvironmentthatmaybeinfluencedbyitsoperation.Eachrequirementsourceisthen consideredtobeaviewpoint.AlthoughVORDpresentsomepointsofweaknessaccordingto authorsin (Kotonya,&Sommerville,1996).Goal-OrientedRequirementEngineering(GORE)isa sub-areaofRE,whichaddressesusingofgoalsforeliciting,elaborating,structuring,specifying, analyzing,negotiating,documenting,andmodifyingrequirements (Lamsweerde,2009).Goalorientedapproachesofferexplicitsupportfordealingwithhigh-leveluserandstakeholders'goals makingiteasiertoconsiderdesignsolutionsandtoidentifycriteriaatanacceptablelevelof abstraction (Kolos,Eck,&Wieringa,2005).Duringtheearlyrequirementsphase,i* (Yu,1997) frameworkisusedtomodeltheenvironmentofthesystem-to-be.Itfacilitatestheanalysisofthe domainbyallowingthemodelertodiagrammaticallyrepresentthestakeholdersofthesystem, their objectives, and relationships.…”
Section: Introductionmentioning
confidence: 99%